Antifungal potential "in vitro" of foliar extracts of Justicia L. (Acanthaceae) species against veterinary clinical isolates of dermatophytes (Research, Society and Development, 2022)
Dermatophytes are keratinophilic fungi, which digest the keratin of skin, hair and nails, using it as a nutrient. By this nature they are able to invade these tissues, thus causing infections called dermatophytosis. One of the main classes of antifungals used in the treatment of dermatophytosis is the azoles. Due to the increasing resistance of fungi to these drugs, new compounds are increasingly being sought in order to overcome this problem. Justicia paracambi and Justicia wasshauseniana are native plant species to the Brazilian territory, which belong to a genus known to have medicinal properties. Thus, the objective of the present work was to evaluate the activity of commercial antifungal agents, and the antifungal activity of hydroalcoholic and aqueous extracts of J. paracambi and J. wasshauseniana on dermatophytes from veterinary clinical samples. Assays were performed using the paper disk diffusion technique as described by Kirby-Bauer, using extracts from the leaves of the aforementioned plants and commercial antifungal disks. According to the results, ketoconazole showed the highest antifungal activity and miconazole the lowest. Regarding the extracts, the aqueous of J. paracambi showed higher antifungal activity. It is concluded that J. paracambi and J. wasshauseniana have antifungal potential to be explored as an alternative to traditional commercial drugs, mainly by observing the zones of inhibition produced by the aqueous extract of J. paracambi.